On the Economics of Road Congestion - Johnson, M. Bruce (Econometrica, 1964)
This paper presents a model in which (1) the market demand for urban automobile travel is a function of a time-price as well as a money-price and (2) the market supply is represented by a flow function that is derived from assumed relationships between traffic density and average speed. Two qualitatively different types of traffic congestion are identified. Marginal cost pricing in terms of both time and money taxes is proposed as an efficient and feasible means of controlling both types of traffic congestion. Using the results of existing empirical studies, tax schedules for three types of urban roads are computed. THERE APPEARS to be unanimous agreement that traffic congestion is prevalent in contemporary urban areas and that certain social costs are incurred as a consequence. The more important questions: how to measure these social costs and how to reduce or eliminate them, remain under debate. Arguing from the premise that the essential physical nature of traffic congestion must be clarified before measurement and remedial action are possible, this paper attempts to (1) define traffic congestion in a precise fashion, (2) develop a model consistent with both traditional price theory and this formal notion of congestion, and (3) bring available empirical evidence to bear on the implications of the model. The analysis rests on the proposition that both time costs and dollar operating costs of automobile trips are relevant to the individual decision process. Formally, it is assumed that individuals face time-price parameters as well as dollar-price parameters and that market demand functions for automobile trips can be expressed in terms of these parameters.